A weak messianic power : figures of a time to come in Benjamin, Derrida, and Celan - Levine, Michael G. (Fordham University Press, 2014)
A weak Messianic power serves as the focal point for this study of theological, materialist, poetic, and post-Freudian psychoanalytic approaches to time and the historical unconscious in the work of Benjamin, Celan, and Derrida.